Salivary proteins and glycoproteins in phlebotomine sandflies of various species, sex and age - Volf, P; Tesarová, P; Nohýnkova, E N (Medical and veterinary entomology, 2000)
Salivary gland proteins were studied in sandflies (Diptera: Psychodidae: Phlebotominae) by electrophoretic techniques. In Phlebotomus duboscqi Neveu-Lemaire the protein concentration was about 30 times higher in females than in males. SDS PAGE revealed eight major bands of 29-62 kDa in salivary gland extracts (SGE) from females, whereas only one band of 57kDa was detected in males. The number of protein components in SGE gradually increased with the age of females. In P. papatasi (Scopoli) the typical electrophoretic pattern was reached in 3-5 days after imago emergence, depending on the temperature at which females were maintained. All major protein components of the female SGE were present in the content of glands. Female SGE were compared in seven colonies of five Phlebotomus and Lutzomyia species; electrophoretic profiles distinguished between species and even between colonies of different geographical origin. In general, the highest variability of major protein components was observed in the 38-48kDa region. Four colonies of the subgenus Phlebotomus (P. duboscqi and P. papatasi) possessed common mobility polypeptides, the highest similarity was found between two colonies of P. papatasi. Other species tested significantly differed, specific prominent bands of 33, 35 and 38kDa were found in P. halepensis Theodor, P. perniciosus Newstead and Lutzomyia longipalpis (Lutz & Neiva), respectively. Glycoproteins in SGE of Lu. longipalpis and P. duboscqi females were identified and analysed using blotting with five lectin conjugates. Specific reaction of lectins ConA and WGA revealed the complex type of N-glycans in the 48 and 53-54kDa glycoproteins present in both species. Similar glycosylation was detected in species-specific bands of the 57-60 and 65-67 kDa in P. duboscqi and Lu. longipalpis, respectively. The high mannose type of glycosylation was found in the 20 and 39 kDa polypeptides of Lu. longipalpis and the 40-42 kDa polypeptides of P. duboscqi. Innate lectin activity specific for aminosugars was detected in SGE of P. duboscqi females using haemagglutination tests with rabbit erythrocytes.
Keywords: Electrophoresis, Polyacrylamide Gel; elektroforéza v polyakrylamidovém gelu; Salivary Proteins and Peptides; molekulová hmotnost; Female; slinné proteiny a peptidy; věkové faktory; lektiny; zvířata; glykoproteiny; Lectins; ženské pohlaví; glykosylace; Glycoproteins; králíci; Age Factors; Animals; Polysaccharides; polysacharidy; Psychodidae; Glycosylation; Rabbits; Molecular Weight